Resolution and Characterization of Helicate Dimer and Trimer Complexes of 1,3-Bis(9-Methyl-1,10-Phenanthrolin-2-Yl)Propane with Copper(I) - Costamagna-Martra, J; Costamagna-Martra, J; Guerrero-Nunez, J; Guerrero-Nunez, J; Lemus-Chavez, L; Lemus-Chavez, L; Lorca-Contreras, R; Lorca-Contreras, R (2013)
Complexation of copper(i) with the binucleating ligand, 1,3-bis(9-methyl-1,10-phenanthrolin-2-yl)propane, mphenpr, result in formation of helical dimers, [Cu2(mphenpr)2]2+. The resolution of the enantiomeric forms of the dimers has been carried out with ?-[As(cat)3]- as resolving agent and X-ray structures for two compounds, P-[Cu2(mphenpr)2](?- [As(cat)3])2 and P-[Cu2(mphenpr) 2](?-[As(cat)3])2·4(CH 3CN), are reported. The rate of racemization in poorly-coordinating solvents has been examined by 1H NMR, and is slow. At saturating concentrations of [[Cu2(mphenpr)2]2+] in acetonitrile, crystals of the helical trimeric complex [Cu3(mphenpr) 3](ClO4)3 are obtained. The X-ray structure of the trimer is reported. This species has also been resolved. As with the helical dimer, racemization in poorly-coordinating solvents is slow, and circular dichroism and 1H NMR spectra are reported. The absolute configuration of the resolved complex, P-[Cu3(mphenpr)3](?- [As(cat)3])3, has been determined by X-ray crystallography. © 2013 The Royal Society of Chemistry.